Game Pembelajaran Bahasa Inggris Bertema Pelestarian Lingkungan Sungai Dengan Pengembangan Animasi Flash Berbasis Android - Suyanto, Budi; Hestiningsih, Idhawati; Fardana, Budi (Teknik Elektro - Politeknik Negeri Semarang, 2017)
With the development of recent technology, English became compulsory language we must mastered. English grammar which is different from Indonesia grammar are being one of the obstacles in doing communication using English. Moreover, English learning system that used today still fixated on printed books and learning activity in schools or other education institutions causing people easily bored and tired. From the existing problem, GRAMER as English edugame with river preservation theme are created. Methods used in this research are Waterfall method, in this method, every research steps performed sequentially, start from Analytical Needs, System Design, Implementation and Unit Testing, Integration and System Test and Operation and Maintenance. System planning using Use Case UML Model. System development using Adobe Flash CS6 and using ActionScript3 programming language. System are tested by testing every application functions on 3 Android devices, with JellyBean, KitKat and Lolipop Operating System. This system are tested with result 80,4% of user satisfaction level.Â Keywords: English, Environmental Conservation, Flash, Game, Grammar